Mucin-producing tumor of the pancreas: a case report - Hasan ÖZKAN; Hiromitsu SAISHO; Taketo YAMAGUCHI; Takeshi ISHIHARA; Toshio TSUYUGUCHI; Yasuharu KIKUCHI; Masao OHTO (Turkish Journal of Gastroenterology, 2020)
-